2014
DOI: 10.1080/00325481.2015.994879
|View full text |Cite
|
Sign up to set email alerts
|

rsfMRIeffects of KB220Z™ on neural pathways in reward circuitry of abstinent genotyped heroin addicts

Abstract: Recently Willuhn et al. reported that cocaine use and even non-substance related addictive behavior, increases, as dopaminergic function is reduced. Chronic cocaine exposure has been associated with decreases in D2/D3 receptors, also associated with lower activation to cues in occipital cortex and cerebellum in a recent PET study from Volkow’s group. Therefore, treatment strategies, like dopamine agonist therapy, that might conserve dopamine function may be an interesting approach to relapse prevention in psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 62 publications
6
97
0
Order By: Relevance
“…We think that the stress of long term therapy should be restricted only to a small subset of individuals who are resistant to short-term treatment. For some of these individuals pharmacotherapy or other forms of dopamine agonistic therapy [23,24] may be effective for some but not all, while others may benefit from psychological and social interventions, which should be used to maximize benefits of the short-term treatment. We can achieve better outcome with this approach without adverse consequences of long-term use.…”
Section: Resultsmentioning
confidence: 99%
“…We think that the stress of long term therapy should be restricted only to a small subset of individuals who are resistant to short-term treatment. For some of these individuals pharmacotherapy or other forms of dopamine agonistic therapy [23,24] may be effective for some but not all, while others may benefit from psychological and social interventions, which should be used to maximize benefits of the short-term treatment. We can achieve better outcome with this approach without adverse consequences of long-term use.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative electroencephalographic (qEEG) studies in humans have found that KB220Z modulates theta power in the anterior cingulate cortex. In abstinent heroin addicts, a single dose of KB220Z compared with placebo in a pilot study (Blum et al 2014b) resulted in activation of the NAc as well as activation and improvement of the prefrontal-cerebellar-occipital neural network. In addition, it was found that carriers with the DRD2 A1 allele showed a significant Pearson correlation in terms of enhanced compliance to KB220Z treatment relative to carriers of the normal compliment of DRD2 receptors in known obese patients (Blum et al 2014b).…”
Section: Dopamine Agonist Therapy: Reasons For Blocking Rewardmentioning
confidence: 99%
“…potentially play important roles in heroin addiction. Most recently Blum's laboratory along with Zhang's group [23] in abstinent heroin addicts showed that KB220Z™ a complex putative dopamine D2 agonist, induced an increase in BOLD activation in caudate-accumbens-dopaminergic pathways compared to placebo following one-hour acute administration. Furthermore, KB220Z™ also reduced resting state activity in the putamen of abstinent heroin addicts.…”
Section: Can We Predict Risk Using Genetic Testing?mentioning
confidence: 99%